BOOMING SENI LUKIS INDONESIA, SIAPA YANG DIUNTUNGKAN? - Satriana Didiek Isnanta (Institut Seni Indonesia Surakarta, 2016)
In the development of fine art in Indonesia there was once an interesting phenom- enon, namely, â€œpainting boom.â€ Â It first happened in 1987, then in 1991-1992, in